2017
DOI: 10.1590/1980-5373-mr-2017-0347
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behaviour of Electroless heat Treated Ni-P Coatings as Alternative to Electroplated hard Chromium Deposits

Abstract: In this present study was evaluated the influence of heat treatment on the wear resistance of electroless high phosphorus nickel coating (9-10% P wt.). In addition, both untreated and treated Ni-P deposits were then compared to electroplated hard chromium coatings in terms of wear behaviour. Three different heat treatment conditions were performed at temperatures of 320ºC, 400ºC and 500ºC under different holding times. The selection of the heat treatment conditions was chosen considering the results obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…They concluded that the heat-treatment results in the formation of the Ni 3 P phase on the coated surface are responsible for enhancing hardness. Goettems & Ferreira (2017) found that electroless Ni-P deposits with post-heat-treatment at 320°C (9 h) and 400°C (1 h) have shown a better wear resistance than electroplated hard chromium coating. They also concluded that this is due to the formation of nickel crystallites and nickel phosphides (Ni 3 P).…”
Section: Public Interest Statementmentioning
confidence: 96%
See 1 more Smart Citation
“…They concluded that the heat-treatment results in the formation of the Ni 3 P phase on the coated surface are responsible for enhancing hardness. Goettems & Ferreira (2017) found that electroless Ni-P deposits with post-heat-treatment at 320°C (9 h) and 400°C (1 h) have shown a better wear resistance than electroplated hard chromium coating. They also concluded that this is due to the formation of nickel crystallites and nickel phosphides (Ni 3 P).…”
Section: Public Interest Statementmentioning
confidence: 96%
“…This structure also influences the wear resistance of the electroless Ni-P. It has been reported in the literature that, due to Ni--P coating on steel, improved tremendous wear resistance after heat treatment at 320°C and 400°C (Samuel & Zoppas, 2017;Uday Venkat Kiran et al, 2019).…”
Section: Wear Testmentioning
confidence: 99%
“…The formation of nodules mainly depends upon the rate of nickel deposition. For example, the size of the nodule decreases with increase in the nickel deposition [27] and vice versa. Similarly for the reinforcement of CaBr 2 , the high rate of nickel deposition has affected the nodular formation.…”
Section: Surface Characterizationmentioning
confidence: 99%
“…These coatings are based on conventional binary Ni-P films and have consolidated engineering applications in the automotive, aerospace, and food industries [13]. They owe their outstanding performance to a combination of strong adhesion in a variety of substrates, shapes and sizes, and high hardness in the annealed state, due to the precipitation of nickel phosphides promoting good wear and corrosion resistance [14,15]. In recent decades, further developments in the electroless deposition of nickel-based coatings have been driven by growing needs for optimized surface properties of metallic materials to expand their applicability to more aggressive environments.…”
Section: Introductionmentioning
confidence: 99%